Analisis Efektivitas Pemungutan Bea Perolehan Hak Atas Tanah Dan Bangunan (BPHTB) Dalam Rangka Meningkatkan Penerimaan Pajak Daerah Di Unit Pelayanan Pemungutan Pajak Daerah (UPPPD) Kecamatan Koja Pada Tahun 2020-2022 - Arda Ika Aslami; Mira Permata Sari (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Background: in 2020-2022 BPHTB revenue has failed to meet the predetermined BPHTB target. The highest achievement was only 87.53%. This study aims to analyze the effectiveness of collecting LBRAF (Land and Building Rights Acquisition Fees) in order to enhance local Tax Revenue at the Koja District RTCSU (Regional Tax Collection Service Unit) between 2020 and 2022. Additionally, it aims to identify the challenges encountered and the efforts made by the Koja District RTCSU (Regional Tax Collection Service Unit) in conducting this analysis. The research adopt a qualitative descriptive approach, employing data collection techniques such as Interviews, Observation, Documentation, and Triangulation. Interviews were conducted with key stakeholders including the Head of the Collection Unit, the Head of the Koja District RTCSU (Regional Tax Collection Service Unit), Academics, and Taxpayers. The findings indicate that the collection of LBRAF (Land and Building Rights Acquisition Fees) has been ineffective, evident from the failure to achieve the annual collection targets. However, this is juxtaposed with fluctuations in the issuance of RTPC (Regional Tax Payment Certificates) over the years. The low level of Taxpayer Awareness in reporting and Paying Taxes, as well as suboptimal socialization efforts, are identified as key contributing factors. The study identifies challenges including a limited number of Tax Officers, inadequate Taxpayer understanding of Technology, and highlights the Service Unit’s efforts, such as conducting socialization activities, improving services, supervising the collection process, enforcing legal sanctions for Tax Violators and other using social media